2013
DOI: 10.1021/ie4022732
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Flow Structures around Side-by-Side Spheres

Abstract: The flow characteristics of a single and the two side-by-side spheres immersed in a uniform flow for Re = 5 × 103 are studied qualitatively and quantitatively employing dye visualization and a particle image velocimetry. The current study focuses on the analysis of the flow behavior using instantaneous and time-mean flow data in plan-view and cross-sectional planes. Flow features and distributions of velocity vectors, V*, at the critical locations; patterns of velocity fluctuations, u* and v*; contours of sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…In these formations apart from the non-dimensional streamwise distance between the droplets (L/D0), also the cross-stream one (H/D0) can be speculate to play a role; the L and H here correspond to distances between the droplet centres. Regarding the hydrodynamic interaction between rigid particles, the experimental works of [7,8] examined two particles exposed in parallel to a uniform flow of water, with non-dimensional distances between them (H/D0) ranging from 1 up to 2.5 and Re number equal to 5,000. They studied mainly the flow around the particles and concluded that for H/D0=1 (particles are in contact) the particles act as a rigid bluff body, while for H/D0≥2 the interaction between the shedding vortices is minimized as well as the effect of the jet-like flow occurring through them.…”
Section: Introductionmentioning
confidence: 99%
“…In these formations apart from the non-dimensional streamwise distance between the droplets (L/D0), also the cross-stream one (H/D0) can be speculate to play a role; the L and H here correspond to distances between the droplet centres. Regarding the hydrodynamic interaction between rigid particles, the experimental works of [7,8] examined two particles exposed in parallel to a uniform flow of water, with non-dimensional distances between them (H/D0) ranging from 1 up to 2.5 and Re number equal to 5,000. They studied mainly the flow around the particles and concluded that for H/D0=1 (particles are in contact) the particles act as a rigid bluff body, while for H/D0≥2 the interaction between the shedding vortices is minimized as well as the effect of the jet-like flow occurring through them.…”
Section: Introductionmentioning
confidence: 99%
“…The system PIV system used in this work was extensively described in [34,35]. Thus, data needed for the evaluation of the results are presented here.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
“…PIV allows for practically nonintrusive measurement of the velocity field in contrast to point measurements using other methods that provides plenty of data for validation. Recently, several studies have been done by different researchers in a variety of geometries (Chen and Wu, 2000;Johnson and Patel, 1999;Liang et al, 1996;Maheshwari et al, 2006;Ozgoren, 2013;Ozgoren et al, 2014Ozgoren et al, , 2013Ozgoren et al, , 2011Pinar et al, 2013;Prahl et al, 2007;Tsuji et al, 2003Tsuji et al, , 1982Zhu et al, 1994). This chapter is an article published in Chemical Engineering Journal (Ramezani et al, 2015).…”
Section: Flow Field Investigation Around a Train Of Particles In A Sqmentioning
confidence: 99%
“…Recently, several studies have been done by different researchers in a variety of geometries (Ozgoren, 2013;Ozgoren et al, 2013Ozgoren et al, , 2011Pinar et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation